Modified Van Assche magnetic resonance imaging-based score for assessing the clinical status of anal fistulas - Wang, Wei-Guo (Medicine (Baltimore), 2020)
The modified Van Assche magnetic resonance imaging (MRI)-based score is a feasible system to assess the clinical status of anal fistulas in Crohn disease. In this study, we evaluated this score's association with clinical status in patients with anal fistulas (AFs). We included all patients with AF who underwent contrast-enhanced pelvic MRI and surgery between January 2011 and December 2016. The score was evaluated retrospectively preoperatively and 1, 3, and 6 months postoperatively. Univariate and multivariate analyses of the risk factors for AF recurrence were also performed. We retrospectively analyzed data for 104 patients. Twelve (11.5%) patients developed AF recurrence. We classified patients’ preoperative clinical status into three grades: 52 (50.0%) grade A, 31 (29.8%) grade B, and 21 (20.2%) grade C. The preoperative MRI-based score was significantly correlated with patients’ preoperative clinical status grade (Pearson correlation: 0.547; P < .001). The 3 preoperative clinical status grades showed significant (F = 23.303, P < .001) tendencies for associations with lower respective MRI-based scores. The incidence of AF recurrence decreased with the MRI-based score to 1-month postoperatively, then gradually increased (F = 60.863, P = .000). Long duration of disease, prior interventions, and high MRI-based score were independent risk factors for AF recurrence. The MRI-based score objectively assessed the clinical status and disease activity of patients with AFs, with a high score being associated with severe clinical status and long recovery time.